Exploring meaning-making among those who are identified by scientists as vaccine-resistant, vaccine-hesitant, or vaccine-sceptical - Ngomane, Tsholofelo (School of African and GenderStuds, Anth and Ling, 2025)
Vaccines are an indisputable human right and an important tool in the advancement of world health. Over the last few decades, their function in disease prevention and outbreak management has been increasingly important. Immunization is considered an important investment in one's health, and in South Africa, childhood immunization is an important and effective public health intervention. South Africa uses an opt-out vaccination system. Children receive their first dose of vaccines upon birth unless their parent states otherwise and continue to receive a standard series of vaccinations for common illnesses throughout childhood. These include vaccinations for the BCG, Polio, Rotaviruses, Pneumonia, and Diphtheria. They also receive vaccinations for tetanus, acellular pertussis, inactivated polio vaccine, and a combination of Haemophilus influenzae type B and hepatitis B and measles. Vaccinations and boosters continue until 18 months old. Thereafter, girls and boys ages 6 and 12 receive the Td Vaccine (Tetanus and reduced strength of the Diphtheria Vaccine). Children also receive voluntary vaccines such as the Flu vaccine throughout their lives and the Human Papillomavirus HPV vaccine is given to girls from as early as 9 years and they usually receive a boost later. This suggests that vaccination is already an ordinary part of most South African lives. However, faced with COVID-19, debates erupted about the value, efficacy, and role of vaccinations in the prevention of illness. The dissertation explores debates about vaccination as they arose amid the pandemic. Drawing on three months of research conducted in 2022-3, it reflects on the social anxieties that the vaccine evoked and the nuances of simplistic accounts of vaccine resistance. Several factors have been identified as influencing vaccination resistance. Some are related to mistrust of biomedicine (due, in part, to previous histories of biomedical experimentation and the apartheid state's harmful practices); others are related to specific ideas about the body and how it should be treated, and still, others are related to a lack of access to basic health care resources or negative experiences in state institutions. Some people are skeptical of Covid-19; some are motivated by religious beliefs about post-infection immunity, and some may be the result of specific ways of conceptualizing the relationship between life cycle and risk. The thesis explores people's ideas about vaccination, focusing on those who were ‘vaccine skeptical' and ‘vaccine-hesitant'. It shows that their hesitancy to vaccinate for Covid-19 was influenced by different factors. For most people ‘Time' played a big role in their hesitancy and skepticism to vaccinate. They questioned the time it took to develop the vaccine and presented it to the public and, given both the speed of vaccine development and prior histories of medical abuse, they were reluctant to present their bodies to be used for trials. Another factor that influenced hesitancy was motivated by religious beliefs. Pentecostal Christians in particular did not want to vaccinate because they feared that the vaccine contained “the mark of the beast 666”. The number “666” is associated with the devil by many Christians and they did not want to put themselves in a position that compromised their faith. Social media also had an effect in influencing people to be hesitant to vaccinate, as it is a public platform where people can say anything and that information can be misleading and yet people make decisions based on it. The need to prevent material flow resulted in people not wanting to vaccinate. They believed that the pandemic was politically motivated and a money-making scheme where big pharmaceuticals, the government, and big business people stood the chance to benefit from it hence they did not want to contribute to it by using their bodies. The end result was distrust in the vaccine and the vaccination process.